The Beginnings of Stage Directing in the Romanian Theatre. A Historical View - MIHALACHE, Alina Gabriela (Studia Universitatis Babeș-Bolyai Dramatica, 2024)
Lacking a consolidated tradition in the art of stage acting and directing, the Romanian national theatres, which had only existed for a few decades, faced a series of legislative, administrative and aesthetic reforms at the beginning of the 20th century. These reforms aimed to acclimatize the most important novelties of modern performance, just emerging on Western stages. Such changes strongly impacted the conservative world of declamation and rhetoric, still indebted to the Romanticist school of theatrical interpretation. This paper aims to provide a cultural-historical perspective on the generational and artistic conflict that led to the modernization of the Romanian mise-en-scène and to the consolidation of the director’s status, in the “century of directing”, focusing on Alexandru Davila’s contribution to the process.